TRIBUTE TO TABLA LEGEND ZAKIR HUSSAIN - Bhandari, Sugandhi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
An integral part of Indian Classical Music, Tabla is one of the most popular musical instruments worldwide. Because of its diversity in many other music styles, today Tabla is one of the most used percussion instruments. While the history of tabla is unknown, modern research suggests that it was invented around 1738 by poet, singer, drummer, and scholar Amir Khusro. This led to invention of a new music style called Khayal.